Evaluation of Zucchini (Cucurbita pepo L.) Genotypes for Spring Season Production in the Mid–Hills of Nepal - Shrestha, SurendraLal; Dhakal, Mira; Sapkota, Sangeeta; Gautam, Ishwori Prasad; Pandey, Suprabha; Shrestha, Yadav (Nepal Journal of Science and Technology, 2021)
Zucchini (Cucurbita pepo L.) is one of the most popular and demanded vegetable in Nepal. Seedlings of seven genotypes of squash gourd; Super Squash Ball, Squash Long, Squash Light, Squash Green Ball, Squash Green House Sondo V (check) and Grey Zucchini (check) were transplanted on second week of March in two consecutive years; 2016 and 2017 in field condition at Khumaltar with a spacing of 90 x 90 cm in four replications. The standard recommended dose of fertilizers (240:180:60 NPK kg/ha + 15 ton FYM/ha) and minimum pesticide and fungicide was applied. The main objective of this experiment was to find out suitable high yielding and insect pest and disease tolerant hybrid Zucchini cultivars for commercial production in mid-hills of Nepal. Crops were evaluated for their vegetative, insect pest and disease, and yield attributing parameters. Among the tested genotypes; Squash Long was found highly uniform, vigorous, least virus and insect damage, significantly higher number of fruits(8.6), and yield (3894 g) per plant and yield (46.89 t/ha) followed by Super Squash Ball having highly uniform, less insect and powdery mildew damage, significantly higher number of fruits (8.5) and yield (2565 g) per plant and yield (29.28 t/ha) as compared to check Sondo V and Grey Zucchini where Sondo V had yield (22.50 t/ha and 1703 g/plant), number of fruits (5.6), per plant respectively. Squash Long and Super Squash Ball have been selected and recommended for cultivation during spring season in mid-hills of Nepal.